Online Classes During Covit-19: Experiences of Public Sector High School Teachers in Khyber Pakhtunkhwa, Pakistan - Ayub Khan; Zahidullah; Alam Zeb; Saba Hassan (Formosa Journal of Multidisciplinary Research, 2023)
The qualitative study investigated problems faced by high school teachers in delivering online classes during COVIT-19. Data were collected from 45 government high school teachers in district Swat through open-ended interview. Using coding and categorizing, four themes were emerged: Unavailability of proper devices to students, Weak and fluctuating internet signals in rural areas, Installation and effectiveness of various App(s) in the device, and Non-serious attitude of students to attend online classes. The provision of free devices along with strong internet services to the students, essential training regarding the installation and use of devices and initiate a parallel program of paper-pen home assignments for the better teaching-learning process in such challenging times of pandemic may be made sure.